MUC13 overexpression in renal cell carcinoma plays a central role in tumor progression and drug resistance. Issue 10 (28th February 2017) - Sheng, Yonghua; Ng, Choa Ping; Lourie, Rohan; Shah, Esha T.; He, Yaowu; Wong, Kuan Yau; Seim, Inge; Oancea, Iulia; Morais, Christudas; Jeffery, Penny L.; Hooper, John; Gobe, Glenda C.; et al.
Abstract : Metastatic renal cell carcinoma is a largely incurable disease, and existing treatments targeting angiogenesis and tyrosine kinase receptors are only partially effective. Here we reveal that MUC13, a cell surface mucin glycoprotein, is aberrantly expressed by most renal cell carcinomas, with increasing expression positively correlating with tumor grade. Importantly, we demonstrated that high MUC13 expression was a statistically significant independent predictor of poor survival in two independent cohorts, particularly in stage 1 cancers. In cultured renal cell carcinoma cells MUC13 promoted proliferation and induced the cell cycle regulator, cyclin D1, and inhibited apoptosis by inducing the anti‐apoptotic proteins, BCL‐xL and survivin. Silencing of MUC13 expression inhibited migration and invasion, and sensitized renal cancer cells to killing by the multi‐kinase inhibitors used clinically, sorafenib and sunitinib, and reversed acquired resistance to these drugs. Furthermore, we demonstrated that MUC13 promotion of renal cancer cell growth and survival is mediated by activation of nuclear factor κB, a transcription factor known to regulate the expression of genes that play key roles in the development and progression of cancer. These results show that MUC13 has potential as a prognostic marker for aggressive early stage renal cell cancer and is a plausible target to sensitize these tumors to therapy. Abstract : What's new? New prognostic markers and therapeutic targets are needed for renal cell carcinoma (RCC). Here, the authors show that cell surface mucin glycoprotein MUC13 is aberrantly expressed in RCC and associated with poor survival. In cultured RCC cells, MUC13 promotes growth and blocks apoptosis. Silencing of MUC13 expression inhibits migration and invasion, sensitizes renal cancer cells to killing by the multi‐kinase inhibitors used clinically (sorafenib and sunitinib) and reverses acquired resistance to these drugs. Thus, MUC13 has potential as a prognostic marker for aggressive early stage renal cell cancer and emerges as a plausible target to sensitize these tumors to therapy.